Kontribusi Play Assessment Chart terhadap Guru SLB-C untuk Kegiatan Asesmen dalam Penyusunan Program Pembelajaran Individual - Bandi Delphie (Universitas Negeri Malang, 2016)
The Play Assessment Chart is aimed at investigating the functional skills of mentally retarded students in applying individualized educational program. Data were gathered from nine special schools for the mentally retarded (SLB-C). The data were analyzed before and after assessment through T-test; and the results show there is a significand difference between pre test and post test data.